Pengaruh Umur Simpan Brownies Kukus Ampas Tahu Pada Suhu Ruang dan Suhu Dingin - Sofnitati, Sofnitati (Universitas Dr Soetomo, 2018)
Steamed oilcake tofu brownies is belong to a semi-wet type of food that easy breaks down and has a relatively short shelf life. Determination of shelf life is the determination of expired date by shelf life a series of products under normal conditions everyday and made observations of the quality decrease to reach the quality level of expiration, so that the food can not be consumed anymore. shelf life was done by looking at the quality degradation reaction using storage with different temperature between normal temperature (room temperature) and cold temperature (refrigerator) and simulate the data obtained. The using method in this research is descriptive qualitative by observing the influence of steamed oilcake tofu at room temperature and cold temperature for 12 days, to the quality of volume, shape, color, aroma, texture and taste. The result of the research showed that the age of steamed oilcake tofu at room temperature showed significant change on the 4th days and 12th days, to the color, aroma and taste quality, while the quality of volume and shape did not change. Shelf life steamed oilcake tofu knows at cold temperatures there is significant changes on day 10th and day 12th on taste and texture quality, while on quality of volume, shape and color there is no change. From the results of this study it can be concluded that the age of the steamed oilcake tofu brownies at room temperature is 3 days, and shelf life of steamed oilcake tofu brownies at cold temperatures is 9 days.Keywords: Shelf Life; Steamed Tofu Brownies; Temperature